(3GdeZjK aj GdWHs - (3CHh Ydj CMeO Hf YHO GdQMef, GHf efOhjg GdCUagGfj,J (B372 (3g` s
(3ChdgG (B:s
(3gPG edJbW ef ahGFO GdcJGH GdeSei HGdeZjK ai GdWH GdMeO ddg GdLRjd YWGDg GdLejd HdGDg hHYO Cf Chd eG jLH Ydi GdCfSGf Ydeg hdGjSYg JQcg GdJabg ai GdOjf hGdfXQ ai GdWH s
(3BNQgG (B:s
(3GdTQHI efg OQge hfUa Edi OQgejf Je GdcJGH HaVd Gddg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3HgG fXGe GdJYbjHIs
(3LRA efgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs